Biological and environmental effects on fine-scale seed dispersal of an invasive tree in a secondary subtropical forest - Powell, Priscila Ana (2018)
Dispersal abilities of invading species emerge from the interaction between the species and some features of the target community. Ligustrum lucidum is a tree species invading different ecosystems. Major spatial patterns of Ligustrum invasions and their ecological consequences have been analyzed, but no study addressed the dispersal process at a fine scale, assessing the effects of different biological and environmental factors. Ligustrum lucidum is an ornithochoric species. The structure of the environment determines bird movements and thus affects seed dispersal. We used inverse modeling to analyze bird-mediated dispersal of L. lucidum seeds in a secondary Yungas forest and surrounding crop-fields. We assessed the effects of egestion mode (regurgitation and defecation) and tree density (as an environment character) on seed dispersal. Seed dispersal presented different spatial patterns depending on the egestion mode. Tree density was positively associated with the number of regurgitated dispersed seeds and negatively associated with the number of defecated dispersed seeds. In both cases, dispersal distance increased in open areas, but absence of perches inhibited seed arrival. Thus, spread of L. lucidum is facilitated in open areas with some trees; inside the native forest, short distance dispersal facilitates the gradual invasion by this exotic species. Our results suggest that processes like crop abandonment and forest succession, which are active in subtropical montane systems, may facilitate L. lucidum invasion. Our seed dispersal models should be combined with actual distribution maps of L. lucidum to identify areas vulnerable to new invasions.